Aquaculture in Myanmar: Fish farm technology, production economics and management - Belton, Ben; Filipski, Mateusz J.; Hu, Chaoran; International Food Policy Research Institute (Michigan State University, 2017)
Fish farming (aquaculture) has grown rapidly in Myanmar over the last two decades and plays an increasingly important role in national fish supply, but its technical and economic characteristics have been little studied. Feed the Future Innovation Lab for Food Security Policy (FSP) has conducted the first statistically representative survey of fish farms conducted in Myanmar: the Myanmar Aquaculture- Agriculture Survey (MAAS). Features analyzed include: farm productivity and profitability; farm size; production cycle duration; use of feed, seed and other production inputs; demand for labor; harvesting and marketing behaviors; technological change; the economic and social characteristics of fish farming households; and land access and tenure.